PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE DALAM UPAYA MENINGKATKAN HASIL BELAJAR IPS SEJARAH SISWA KELAS VII C SMP ALKAROMAH AIDARUSY KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN AJARAN 2015/2016 - Ainil Hayati; Drs.Marwoto Saiman, M.Pd; Kamaruddin, M.Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the low learning outcomes of students ofclass VII C SMP Alkaromah Aidarusy on History Lesson IPS. The results of studentlearning is still low and does not reach the specified KKM is 70. This is partly due tothe methods used in the study are less precise IPS. The purpose of this study was todetermine the application of learning model Think Pair Share and know the learningoutcome IPS History class VII C SMP Alkaromah Aidarusy through the implementationof learning model Think Pair Share. This research using method classroom actionresearch, which lasted for two cycles. Research action plan, starting from planning,implementation, observation, and reflection. Subjects numbered 18 people. Collectingdata using tests and observation. Data were analyzed by looking at the activity ofteachers and students as well as absorption and mastery learning students bothindividual and classical. The results showed that the learning model Think Pair Sharelearning model can improve the learning process and improve student learningoutcomes. This is evidenced by the increased activity of teacher and students in cycle Iand II. Besides, the learning outcomes of students also increased from indigo pre PTK,cycle I and cycle 2.Keywords: Activities of students and learning outcomes, social studies learning history,learning model Think Pair Share